Correlation between Reactive Stromal Expression and Histochemical Trichrome Masson Staining with Histopathological Grading in Prostate Adenocarcinoma at Adam Malik Haji Center General Hospital Medan - Basrul, Mohd. Yuwanda; Laksmi, Lidya Imelda; Mariedina, Causa Trisna; Lubis, M. Nadjib Dahlan; Intan, T. Kemala; Chrestella, Jessy (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2024)
Background Adenocarcinoma of the prostate is an invasive carcinoma, composed of neoplastic prostatic epithelial cells with differentiation and secretion arranged in various histomorphological patterns.Quantitative analysis of the elements that make up the stroma in casesprostate adenocarcinomahas been linked to prognostic factors and the Gleason score, which correlates with progression and metastasis, and may contribute to new prognostic feature approaches. Method Descriptive analytic study with 33 paraffin block samples diagnosed as prostate adenocarcinoma at Haji Adam Malik General Hospital Medan.Assessment is done forsee the relationship between reactive stromal expression using Trichrome Masson and histopathological grading gleason score then determine the scoring score for the stroma around the prostate gland adenocarcinoma lesion stained blue with trichrome masson, a positive score of one (+): if 0-15% stroma is stained blue, positive two (++): if >15%-<50% stroma is stained and triple positive (+++): if >50% stroma is stained blue. The histopathological grading was categorized into grade I (well differentiated: Gleason score ≤6), grade II (moderately differentiated: Gleason score 7 (3+4)), and grade III (poorly differentiated: Gleason score 7 (4+3) and 8 -10). Results: Reactive stromal expression the most found was positive three (+++) (69.7%) and the most common histopathological grading was grade III (69.7%). There was a significant correlation between reactive stromal expression and histopathological grading in prostate adenocarcinoma (p-value=0.044), namely the worse the cell differentiation, the higher the positive score of reactive stromal expression. Conclusion Assessment of reactive stromal expression associated with histopathological grading can be used as an indication of prognosis in patients with prostate adenocarcinoma.